Human GTPBP5 (MTG2) fuels mitoribosome large subunit maturation by facilitating 16S rRNA methylation - Maiti, Priyanka (Nucleic Acids Res, 2020)
Biogenesis of mammalian mitochondrial ribosomes (mitoribosomes) involves several conserved small GTPases. Here, we report that the Obg family protein GTPBP5 or MTG2 is a mitochondrial protein whose absence in a TALEN-induced HEK293T knockout (KO) cell line leads to severely decreased levels of the 55S monosome and attenuated mitochondrial protein synthesis. We show that a fraction of GTPBP5 co-sediments with the large mitoribosome subunit (mtLSU), and crosslinks specifically with the 16S rRNA, and several mtLSU proteins and assembly factors. Notably, the latter group includes MTERF4, involved in monosome assembly, and MRM2, the methyltransferase that catalyzes the modification of the 16S mt-rRNA A-loop U1369 residue. The GTPBP5 interaction with MRM2 was also detected using the proximity-dependent biotinylation (BioID) assay. In GTPBP5-KO mitochondria, the mtLSU lacks bL36m, accumulates an excess of the assembly factors MTG1, GTPBP10, MALSU1 and MTERF4, and contains hypomethylated 16S rRNA. We propose that GTPBP5 primarily fuels proper mtLSU maturation by securing efficient methylation of two 16S rRNA residues, and ultimately serves to coordinate subunit joining through the release of late-stage mtLSU assembly factors. In this way, GTPBP5 provides an ultimate quality control checkpoint function during mtLSU assembly that minimizes premature subunit joining to ensure the assembly of the mature 55S monosome.